Tephra fall impacts to buildings: the 2017–2018 Manaro Voui eruption, Vanuatu - Jenkins, Susanna F.; McSporran, Ame; Wilson, Thomas M.; Stewart, Carol; Leonard, Graham; Cevuard, Sandrine; Garaebiti, Esline (Frontiers in Earth Science, 2024)
Building damage from tephra falls can have a substantial impact on exposed communities around erupting volcanoes. There are limited empirical studies of tephra fall impacts on buildings, with none on tephra falls impacting traditional thatched timber buildings, despite their prevalence across South Pacific island nations and parts of Asia. The 2017/2018 explosive eruption of Manaro Voui, Ambae Island, Vanuatu, resulted in damage to traditional (thatched timber), non-traditional (masonry), and hybrid buildings from tephra falls in March/April and July 2018. Field and photographic surveys were conducted across three separate field studies with building characteristics and damage recorded for a total of 589 buildings. Buildings were classified using a damage state framework customised for this study. Overall, increasing tephra thicknesses were related to increasing severity of building damage, corroborating previous damage surveys and vulnerability estimates. Traditional buildings were found to be less resistant to tephra loading than non-traditional buildings, although there was variation in resistance within each building type. For example, some traditional buildings collapsed under ~40 mm thickness while others sustained no damage when exposed to >200 mm. We attribute this to differences in the pre-eruption condition of the building and the implementation of mitigation strategies. Mitigation strategies included covering thatched roofs with tarpaulins, which helped shed tephra and consequently reduced loading, and providing an internal prop to the main roof beam, which aided structural resistance. As is typical of post-event building damage surveys, we had limited time and access to the exposed communities, and we note the limitations this had for our findings. Our results contribute to the limited empirical data available for tephra fall building damage and can be used to calibrate existing fragility functions, improving our evidence base for forecasting future impacts for similar construction types globally.